ยุทธศาสตร์การพัฒนาเศรษฐกิจชุมชนบนวัฒนธรรมเศรษฐกิจฐานรากในพื้นที่ฝั่งตะวันออกจังหวัดปทุมธานี (STRATEGIES FOR DEVELOPMENT OF COMMUNITY ECONOMY BASED ON FOUNDATION ECONOMIC CULTURE IN EASTERN AREA OF PATHUMTHANI PROVINCE) - Teetakaew, Torsangravee (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2012)
การศึกษาวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาสภาพบริบท สภาพปัญหาที่เกี่ยวข้องกับการพัฒนาเศรษฐกิจชุมชน ศึกษาวัฒนธรรมเศรษฐกิจฐานราก การพึ่งตนเอง ความเข้มแข็งในชุมชน และเพื่อสร้างและประเมินยุทธศาสตร์การพัฒนาเศรษฐกิจชุมชนบนวัฒนธรรมเศรษฐกิจฐานราก ในพื้นที่ฝั่งตะวันออกจังหวัดปทุมธานี ด้วยวิธีการวิจัยเชิงคุณภาพ กลุ่มตัวอย่าง คือ เกษตรกรดีเด่น ผู้นำชุมชน ประธานวิสาหกิจชุมชน ประธานกลุ่มสหกรณ์การเกษตร และเจ้าหน้าที่ส่วนราชการที่เกี่ยวข้อง จำนวน 33 คน ได้มาจากการเลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัย คือ การสัมภาษณ์เชิงลึก แบบสอบถาม การสังเกตแบบไม่มีส่วนร่วม และการสนทนากลุ่ม สถิติที่ใช้ในการวิจัย ได้แก่ ค่าเฉลี่ย ร้อยละ และส่วนเบี่ยงเบนมาตรฐาน ผลการศึกษาพบว่า ผู้คนส่วนใหญ่ประกอบอาชีพเกษตรกรรม ซึ่งถือว่าเป็นวัฒนธรรมฐานรากที่มีมาช้านาน ปัญหาด้านต่างๆ ที่เกี่ยวข้องและส่งผลกระทบต่อการพัฒนาเศรษฐกิจชุมชนมี 5 ด้าน ได้แก่ 1) ขาดความเข้มแข็งของสังคมและชุมชน 2) ขาดความรู้ความเข้าใจเกี่ยวกับระบบเศรษฐกิจชุมชน 3) ขาดแรงจูงใจให้เกิดค่านิยมที่มีต่อสังคมเกษตรยุคใหม่ เพื่อให้เกษตรกรมีความรักความผูกพันต่อการประกอบอาชีพเกษตรกรรม 4) ขาดความรู้ในการนำทรัพยากรธรรมชาติไปใช้อย่างถูกวิธี 5) ขาดความรู้ในการนำเทคโนโลยีมาใช้อย่างถูกวิธี ยุทธศาสตร์ที่ได้มี 6 ยุทธศาสตร์ ได้แก่ 1) การพัฒนาทรัพยากรธรรมชาติและสิ่งแวดล้อมให้เอื้อต่อการเพาะปลูกนำมาใช้ประโยชน์ให้ได้มากที่สุด 2) การสร้างแรงจูงใจให้เกิดค่านิยมต่อสังคมเกษตรยุคใหม่ และวัฒนธรรมท้องถิ่น เพื่อให้เกษตรกรมีความรัก ความผูกพันต่อการประกอบอาชีพเกษตรกรรม โดยเน้นคนเป็นศูนย์กลางในการพัฒนา 3) การพัฒนาความรู้ของเกษตรกรเพื่อเสริมสร้างศักยภาพการประกอบการ การผลิตการจำหน่าย และการจัดการวิสาหกิจชุมชน 4) พัฒนาศูนย์เรียนรู้เกี่ยวกับเศรษฐกิจพอเพียงที่มีอยู่ในชุมชนเพื่อรักษาไว้ให้เยาวชนหรือผู้สนใจได้ใช้เป็นที่ศึกษาเรียนรู้ แลกเปลี่ยนประสบการณ์ 5) การพัฒนาด้านปัจจัยแวดล้อมด้านระบบเศรษฐกิจชุมชน สังคม ของเกษตรกรให้มีความเหมาะสมกับสภาพการณ์ในปัจจุบัน 6) การพัฒนาการทำการเกษตรแบบปลอดสารพิษ ยุทธศาสตร์ที่สร้างขึ้นมีความเหมาะสมต่อการนำไปใช้ประโยชน์ในการประกอบอาชีพเกษตรกรรม และจะทำให้สามารถสร้างชุมชนให้เกิดความเข้มแข็งแบบสมดุล ส่งผลให้เกิดการพัฒนาเศรษฐกิจชุมชนบนวัฒนธรรมเศรษฐกิจฐานราก ในพื้นที่ฝั่งตะวันออกของจังหวัดปทุมธานีได้อย่างยั่งยืน คำสำคัญ: เศรษฐกิจชุมชน The purposes of this qualitative research were to study the context and problems relating to development of community economy, to find out the foundation economic culture, self-reliance and community strength and to establish and evaluate the strategies for development of community economy based of the foundation economic culture in the eastern area of Pathumthani province. The samples comprised 33 distinct farmers, community leaders, chairpersons of community enterprises, chairpersons of agricultural cooperatives and relevant officials. The research tools consisted of in-depth interview, questionnaires, non-participatory observation and focus group discussion. The statistics utilized in this research were mean, percentage and standard deviation. The research results revealed that the majority of the informants practiced agriculture which was regarded a long-lasting foundation economic culture. There were five problems affected the development of community economy including 1) weakness of society and community, 2) lack of knowledge of community economy system, 3) lack of motivation and value of a new agricultural society to encourage farmers to practice this occupation, 4) lack of right knowledge of consuming natural resources and environment and 5) lack of knowledge of using a proper technology. There were six strategies found in this research: 1) Natural resources and environment were developed for the most benefits of agriculture. 2) Motivation and value of a new agricultural society and local culture was established so that farmers were bound to practice agriculture. People-centered development was also emphasized. 3) Their knowledge was developed to promote their potential for running business, producing, distributing and managing community enterprise. 4) Community sufficiency economy learning center was developed so that youths and those who were interested could study and exchange their experiences at this center. 5) Surrounding factors of system of community economy and society of the farmers were properly developed for present conditions. And 6) Non-toxic agriculture was developed. The constructed strategies were suitable to be applied for their agriculture, strengthened the community in good balance and affected the sustainable development of community economy based on foundation economic culture in the eastern area of Pathumthani province. Keywords: Local community economy